Consumer Loans' First Payment Default (fpd) Detection and Predictive Model - Sevgili, Türkan; Koç, Utku (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL, 2020)
The project is based on the opinion that whether the loan applications which are profitable could be granted instead of prone the default (FPD) ones by using predictive models in machine learning by the credit decision authorities in banking sector. Default Loan (also called non-performing loan) occurs when there is a failure to meet bank conditions and cannot be repaid in accordance with the terms of the loan which has reached its maturity. This report is a research effort in the analysis of default loan applicants, especially FPD, from a real dataset obtained from a bank. Expectation from the study is that increase the efficiency of consumer loan allocation by providing predictive analysis of the consumer behavior concerning loan’s first payment default. FPD detection analysis is a crucial role for the determination of consumer loans at the application level. The study also provides an understanding on the reasons of non-performing loans and helps to manage credit risks more consciously. The methods proposed in this study can be extended to other individual consumer loans such as car credits and mortgage.

Proje, makine öğrenimindeki tahminleme modellerini kullanarak bankacılık sektöründeki kredi karar mercileri tarafından temerrütlü olan krediler yerine karlı olan kredi başvurularının verilip verilemeyeceği konusundan yola çıkılarak hazırlanmıştır. Takipteki krediler (temerrütlü olarak da adlandırılır) borçlunun banka koşullarını yerine getiremediğinde ortaya çıkar ve kredi şartlarına göre vadesinde geri ödenemez. Bu rapor, bir bankadan alınan gerçek bir veri seti üzerinden gerçekleştirilmiş, özellikle İlk Ödemeden Temerrüde Düşen / Ödenmeyen Krediler (FPD) analizine ilişkin bir araştırma çalışmasıdır. Çalışmanın beklentisi, FPD kredilerine ilişkin tüketici davranışının tahminleme analizini sağlayarak tüketici kredisi tahsisinin etkinliğinin artırılmasıdır. FPD tespit analizi, tüketici kredilerinin başvuru aşamasında belirlenmesinde önemli bir rol oynamaktadır. Çalışmanın başka bir amacı da vadesinde geri ödenmeyen kredilerin nedenlerinin anlaşılmasını da sağlayarak, risk yönetimi noktasında daha bilinçli adımlar atılmasına yardımcı olmaktır. Bu çalışmada kullanılan yöntemler, taşıt ve konut kredisi gibi diğer bireysel tüketici kredilerine de uygulanabilir.
Tüketici kredilerinde ilk ödemeden temerrüde düşen/ödenmeyen kredi (FPD) tespiti ve tahminleme modeli
Keywords: Imbalanced class problem; Default loan; Undersampling; Machine learning; First payment default; Oversampling; Bilgisayar Bilimleri, Yazılım Mühendisliği; İşletme Finans; İktisat; Dengesiz sınıf problemi; Consumer loan; Tüketici kredisi; Makine öğrenmesi; Üst-örnekleme; Takipteki kredi; İlk ödemeden temerrüde düşen / ödenmeyen kredi; Alt-örnekleme